Migrating natives and foreign immigration: Is there a preference for ethnic residential homogeneity? - Henrik Andersson; Heléne Berg; Matz Dahlberg (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2018)
In this paper we investigate the migration behavior of the native population following foreign (refugee) immigration, with a particular focus on examining whether there is support for an ethnically based migration response. If ethnicity is the mechanism driving the change in natives' migration behavior, our maintained hypothesis is that native-born individuals who are ethnically similar to arriving refugees should not change their migration behavior to the same extent as native-born individuals with native-born parents (who are ethnically quite different from refugees). Using rich geo-coded register data from Sweden, spanning over 20 consecutive years, we account for possible endogeneity problems with an improved so-called "shift-share" approach; in particular, our strategy combines policy-induced initial immigrant settlements with exogenous contemporaneous immigration as captured by refugee shocks. We find no evidence of neither native flight nor native avoidance when studying the full population. We do, however, find native flight among individuals who are expected to be more mobile, and within this group, we find that all natives, irrespective of their parents' foreign background, react similarly to increased immigration. Our results therefore indicate that preference for ethnically homogeneous neighborhoods may not be the dominant channel inducing flight. The estimates instead indicate that immigration leads to more socio-economically segregated neighborhoods. This conclusion may have implications for the ethnically based tipping point literature.
Keywords: C26; J15; R23; 330; Immigration; Native migration; Flight; Avoidance; IV estimation